Endogenous bioluminescent reporters reveal a sustained increase in utrophin gene expression upon EZH2 and ERK1/2 inhibition - Hannah J. Gleneadie; Beatriz Fernandez-Ruiz; Alessandro Sardini; Mathew Van de Pette; Andrew Dimond; Rab K. Prinjha; James McGinty; Paul M. W. French; Hakan Bagci; Matthias Merkenschlager; Amanda G. Fisher (Communications Biology, 2023)
With the long-term goal of finding therapeutic options for Duchenne muscular dystrophy, a mouse model enabling simultaneous visualisation of Dmd and Utrn is described and inhibitors of PRC2 and ERK1/2 identified to increase utrophin expression.